Life‐history constraints in grassland plant species: a growth‐defence trade‐off is the norm. (24th January 2013) - Lind, Eric M.; Borer, Elizabeth; Seabloom, Eric; Adler, Peter; Bakker, Jonathan D.; Blumenthal, Dana M.; Crawley, Mick; Davies, Kendi; Firn, Jennifer; Gruner, Daniel S.; Stanley Harpole, W.; Hautier, Yann; et al.
Abstract Plant growth can be limited by resource acquisition and defence against consumers, leading to contrasting trade‐off possibilities. The competition‐defence hypothesis posits a trade‐off between competitive ability and defence against enemies (e.g. herbivores and pathogens). The growth‐defence hypothesis suggests that strong competitors for nutrients are also defended against enemies, at a cost to growth rate. We tested these hypotheses using observations of 706 plant populations of over 500 species before and following identical fertilisation and fencing treatments at 39 grassland sites worldwide. Strong positive covariance in species responses to both treatments provided support for a growth‐defence trade‐off: populations that increased with the removal of nutrient limitation (poor competitors) also increased following removal of consumers. This result held globally across 4 years within plant life‐history groups and within the majority of individual sites. Thus, a growth‐defence trade‐off appears to be the norm, and mechanisms maintaining grassland biodiversity may operate within this constraint.